Putusan Serta Merta dalam Perkara Hadhanah di Pengadilan Agama dalam Rangka Perlindungan Anak - Asni, Asni (Fakultas Syariah IAIN Purwokerto, 2021)
Child custody cases processed in the Religious Court often cause certain problems. Therefore, a special strategy is needed by the judge in resolving child custody cases. This paper describes the opportunities for implementing decisions immediately as one of the strategies that can be taken by judges in resolving child custody cases in the Religious Court. A decision immediately is a decision that can be immediately executed even if the opposing party submits legal action. Methodologically, this study uses normative legal research so that it applies a juridical normative approach. The research was conducted by adapting a literature study combined with interviews with Religious Court judges. The results of the study confirm that a decision immediately is one of the strategies that a judge can take if in a case it is feared that the losing party will make negative efforts that can harm the winning party. However, the most important consideration for the judge in this matter is for the best interest of the child and the realization of the benefit of society.